The problems of subsequent typification in genus-group names and use of the Zoological Record: a study of selected post-1930 Diptera genus-group names without type species designations - Evenhuis, Neal L.; Pape, Thomas; Pont, Adrian C. (Zootaxa, 2008)
We list 117 genus-group names of Diptera that were proposed after 1930 with diagnoses and more than one included species but without type species designations and review their current status. Research into the earliest proposals making the names available resulted in one new synonymy: Breviculala Ito, 1949 = Pseudacidia Munro, 1935, n. syn. (Tephritidae), the discovery of a number of earlier designations, and the recognition of available genus-group names previously thought to be nomina nuda. Discussion is made concerning type designations in the Zoological Record and type fixations by monotypy for genus-group names proposed after 1930 without a type species designation.